math

Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find a similar equation for (a - b)2. Examine his argument.
(a - b)2 = [a + (-b)]2
= a2 + 2a(-b) + (-b)2
= a2 – 2ab + b2

  1. 👍 0
  2. 👎 0
  3. 👁 83
asked by jeana
  1. He is correct.

    1. 👍 0
    2. 👎 0
    posted by Henry

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    Kahlil said that using the equation € (a + b)2 = a2 + 2ab + b2, , he can find a similar equation for € (a − b)2 . Examine his argument. If it is correct, supply any missing steps or justification; If it is incorrect point

    asked by Anonymous on September 26, 2011
  2. math 213

    Kahlil said that using the equation he can find a similar equation for Examine his argument. If it is correct, supply any missing steps or justifications; if it is incorrect, point out why. = a2 - 2ab + b2 = a2 + 2a1-b2 + 1-b22 1a

    asked by christy on April 8, 2011
  3. Polynomials

    State whether the following equations are sometimes, always or never true. a) a^2-2ab-b^2= (a-b)^2, bis not equal to 0 b) a^2+ b^2= (a+b)(a+b) c) a^2-b^2= a^2-2ab+b^2 d) (a=b)^2 = a^2+2ab+b^2 I don't understand what these

    asked by Lucina on January 10, 2015
  4. Algebra

    Why does this happen? A=3 and b=2 A+b=c is the equation. Multiplying both sides of the equation makes the equation a^2+2ab+b^2 which is equal to a^2+ab-ac=-ab-b^2+bc Dividing by (a+b-c) we find a=-b or 3=-2 Why?

    asked by Ali on December 3, 2009
  5. algebra

    Is this correct? subtract (4a^3+2b^3)-(6a^3+5a^2b-2ab^2+2b^3) answer: -2a^3-5a^2b+2ab^2

    asked by bb on February 6, 2008
  6. chemistry

    The power of the equation ΔG° = –RT ln(K) is that K can be determined from tabulated values of ΔG°f. Use the tabulated values of the Gibb's energy to determine K for the reaction, 2AB(l) ↔ 2A(g) + B2(g), at 298K. (R=8.314

    asked by Carl on March 15, 2015
  7. factoring completly

    can anyone help me with these: 3x2 + 17x + 10 5y8 - 125 a2 - 2ab - 15b2 4c2 - 12c + 9 5 y^8 - 125 = 5(y^8 - 25) y^8 - 25 can be written (y^4 - 5)(y^4 + 5) For the others, you need to try a few factors until you find a pair that

    asked by mike on March 9, 2007
  8. Math

    I don't understand how this is if (a ± b)² = a² ± 2ab + b² i would think that is would be A squared plus or minues B squared where does the 2ab come from??

    asked by Jon on August 28, 2007
  9. Maths

    A polynomial g(x) is given by: g(x) = (x-1)(x+2)(x-a)(x-b) 1) Given that g(0)=4 show that ab=-2 2) given also that g(3)=40 show that a+b=1 3) given that a and b are integers, give possible values for a and b. My answers 1) g(0) =

    asked by Anonymous on October 15, 2015
  10. algebra

    if a+b=1 and a squared + b squared=2 what does a to the 3rd + b to the 3rd equal? If b is 1, b cubed is one. That would work for the first half, but doesn't extend to a to the 3rd+b to the 3rd and what weould 2 squard be? Thank

    asked by janice on May 13, 2007

More Similar Questions